A Study on the Level of Water Pollution in the Coastal Ecotourism Area of Padang City (Case Study of Bungus Beach, Purus Beach, and Pasir Jambak Beach) - Ridho Qamara; Siti Aisyah; Murhenna Uzra; Ira Desmiati (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The coastal area of Padang City has high ecological and economic potential; however, anthropogenic activities such as tourism, settlements, and industry have contributed to a decline in water quality. This study aims to identify pollutants and determine the pollution status in Bungus Beach, Purus Beach, and Pasir Jambak Beach based on physical, chemical, and biological parameters. A quantitative approach was employed using purposive sampling at three research stations. The observed parameters included temperature, brightness, turbidity, pH, nitrate, phosphate, ammonia, DO, as well as the condition of mangrove, seagrass, and coral reef ecosystems. The data were compared with the marine water quality standards (Government Regulation No. 22 of 2021) and analyzed using the Pollution Index method (Decree of the Ministry of Environment No. 115 of 2003). The results showed that nitrate and phosphate levels exceeded quality standards, DO levels decreased at Purus Beach, and brightness was low in Purus and Pasir Jambak. Biological ecosystems in Purus have disappeared, while Bungus and Pasir Jambak still contain coastal vegetation that is pressured by human activities. Based on the pollution index, Purus is classified as moderately to heavily polluted, while Bungus and Pasir Jambak are classified as lightly to moderately polluted.